Penggunaan Metode Inkuiri Terbimbing Dalam Pengembangan LKS Fisika SMP Kelas VIII Pada Materi Getaran Dan Gelombang - Katayane, Tetrin; Malawau, Seska; Latununuwe, Altje; Sabandar, Vederico Pitsalitz (Physikos: Journal of Physics and Physics Education, 2022)
The research aimed to produce a physics student worksheet (LKS) on vibrations and waves using guided inquiry-based methods. The research conducted refers to the modification of the LKS development model using the 4-D model. Respondents as test subjects in this study consisted of 9 students in class VIII1 on a small scale and 22 students in class VIII3 on a large scale. Based on the results of the research conducted, the eligibility validation results for the LKS were classified as very feasible with an average score of 3.7%, and could be used as a study guide. Meanwhile, the results of the analysis of the legibility of worksheets, both on small-scale and large-scale trials, were classified as high criteria or easily understood by students with an average percentage of acquisition scores on a small scale of 63% and a large scale of 67%. Furthermore, the results of the analysis of student responses to the development of LKS used during the learning process both on a small scale and on a large scale are in very good qualifications with an average acquisition score on a small scale of 92.45% and a large scale of 94.61%. The results of this study indicate that the development of worksheets based on the guided inquiry learning model can make students more active in obtaining information to solve problems given by the teacher so that vibration and wave material can be understood properly.